Relationship between oral clinical conditions and daily performances among young adults in India - A cross sectional study - Ramesh Nagarajappa; Mehak Batra; Sudhanshu Sanadhya; Hemasha Daryani; Gayathri Ramesh (Springer, 2019)
Objective of the present study was to investigate relationship between oral health-related quality of life using Oral Impacts on Daily Performances (OIDP) scale and specific clinical dental measures. A cross sectional descriptive survey was conducted among 800 students. Oral health status and impacts were assessed using WHO guidelines and OIDP index respectively. Chi square test and multiple logistic regressions were employed for statistical analysis. Participants with caries were significantly (p ⩽ 0.05) more likely to have an impact on cleaning (OR = 2.487) and sleeping and relaxing (OR = 8.996). Similarly participants with oral mucosal conditions were more likely to have an impact on eating (OR = 3.97), cleaning (OR = 2.966) and physical activities (OR = 11.190). Dental Aesthetic Index (DAI) impacted on cleaning (OR = 2.134), emotional stability (OR = 3.957) and social contact (OR = 3.21). OIDP Index showed acceptable psychometric properties in the context of an oral health survey. Subjects presented a strong and consistent relationship between dental status and perceived impacts.